2006
DOI: 10.1093/toxsci/kfj164
|View full text |Cite
|
Sign up to set email alerts
|

Ginsenoside Metabolites, Rather Than Naturally Occurring Ginsenosides, Lead to Inhibition of Human Cytochrome P450 Enzymes

Abstract: There is still an argument about ginseng-prescription drug interactions. To evaluate the influence on cytochrome P450 (P450) activities of ginseng in the present study, the influence on P450 activities of naturally occurring ginsenosides and their degradation products in human gut lumen was assayed by using human liver microsomes and cDNA-expressed CYP3A4. The results showed that the naturally occurring ginsenosides exhibited no inhibition or weak inhibition against human CYP3A4, CYP2D6, CYP2C9, CYP2A6, or CYP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
84
1
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(90 citation statements)
references
References 32 publications
4
84
1
1
Order By: Relevance
“…Especially, the metabolites of ginsenosides that are formed by enteric bacteria have been focused on for their pharmacological activities. Among them, compound K (C-K) is known to be formed by enteric bacterial fermentation of Rb1, Rb2 and RC, and C-K has been reported to suppress tumor metastasis and inflammatory responses (6,7). Another ginsenoside Rh2, a metabolite of Rg3, is also known for its tumor suppression by inducing apoptosis or retarding growth signals (8).…”
Section: Proapoptotic Ginsenosides Compound K and Rh2 Enhance Fas-indmentioning
confidence: 99%
“…Especially, the metabolites of ginsenosides that are formed by enteric bacteria have been focused on for their pharmacological activities. Among them, compound K (C-K) is known to be formed by enteric bacterial fermentation of Rb1, Rb2 and RC, and C-K has been reported to suppress tumor metastasis and inflammatory responses (6,7). Another ginsenoside Rh2, a metabolite of Rg3, is also known for its tumor suppression by inducing apoptosis or retarding growth signals (8).…”
Section: Proapoptotic Ginsenosides Compound K and Rh2 Enhance Fas-indmentioning
confidence: 99%
“…Known inhibitors were run in parallel as positive controls: furafylline for CYP1A2, sulfaphenazole for CYP2C9, quinidine for CYP2D6, and ketoconazole for CYP3A4. The (Liu et al, 2006). The K i values were determined by fitting the enzyme activity substrate concentration data at various inhibitor concentrations to the equations for competitive inhibition, noncompetitive inhibition, and mixed-type inhibition.…”
Section: Inhibitory Effects Of Seven Danshen Components On P450smentioning
confidence: 99%
“…Besides, the deglycosylation of saponin to aglycone can also strongly increase the inhibitory effects towards CYPs. Liu et al [21] found that naturally occurring ginsenosides exhibited no inhibition or weak inhibition against human CYPs, while their main intestinal metabolites demonstrated a wide range of inhibition of the P450-mediated metabolism. However, different from the above articles, it is interesting that the intestinal metabolites of icariin exhibited a different inhibition profile compared with icarrin [22].…”
Section: Discussionmentioning
confidence: 99%